The United States in the Anthropocene - Gaetano Di Tommaso (USAbroad, 2024)
This seventh issue of USAbroad aims to look at American history and politics through an environmental lens and reframe the United States’ upward trajectory as a world power in the context of the Anthropocene. In particular, each article offers a unique way to view the intersection of American history, politics, society, and natural resources, showing how the rise of US power—from the late 19th-century imperial project to 20th-century techno-politics—is inextricably linked to the natural elements.